Delays in Autism Diagnosis for U.S. Spanish-speaking Families: The Contribution of Appointment Availability. Issue 2 (3rd April 2022) - Chavez, Alison E.; Feldman, Melanie S.; Carter, Alice S.; Eisenhower, Abbey; Mackie, Thomas I.; Ramella, Leah; Hoch, Noah; Sheldrick, R. Christopher
ABSTRACT: Promoting equity in health services requires an understanding of the mechanisms that produce disparities. Utilizing a sequential, mixed-methods, explanatory study design, we analyzed child-, family-, and organizational-level factors and their association with wait times for an ASD diagnostic evaluation among 353 families scheduled for English and Spanish language appointments (27% Spanish language). A subset of parents and caregivers participated in English and Spanish language focus groups to provide their perspectives on the diagnostic process. Spanish language was associated with greater completion of, and time to evaluations than English language. The only variable found to mediate associations with time-to-evaluation was appointment availability – an organizational factor. Qualitative results elucidate potential explanations for greater Spanish language evaluation completion (e.g., fewer community-based diagnostic options). Results serve as a case study to support the utility and importance of analyzing the influence of organizational-level factors on delays and disparities for childhood health and mental health services. We discuss our findings in relation to strategies that can be widely applied to support equitable services access for childhood diagnostic and intervention services.